2015
DOI: 10.1097/wnr.0000000000000307
|View full text |Cite
|
Sign up to set email alerts
|

Auditory imagery forces motor action

Abstract: A large number of neuroimaging studies have investigated imagined sensory processing and motor behaviours. These studies have reported neural activation patterns for imagined processes that resemble those of real sensory and motor events. The widespread use of such methods has raised questions about the extent to which imagined sensorimotor events mimic their overt counterparts, including their ability to elicit sensorimotor interactions. Direct behavioural evidence of imagery-induced multisensory interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Several studies showed that an auditory stimulus can lead to visual saccades toward the source of the sound (Zahn et al, 1978;Zambarbieri et al, 1982;Van Grootel and Van Opstal, 2009) and that the presentation of an auditory stimulus can reduce the rate of saccades (Rolfs et al, 2005;Kerzel et al, 2010;Yuval-Greenberg and Deouell, 2011;Zou et al, 2012). Moreover, one study has shown evidence that gaze position can affect auditory localization accuracy (Maddox et al, 2014) and results from our team suggest that listening or even imagining auditory motion stimulus can induce involuntary eye movements (Landry et al, 2015). Considering the apparent link between auditory input and oculomotor behaviors, one might wonder how the loss of auditory input from birth might influence these motor behaviors.…”
Section: Introductionsupporting
confidence: 58%
“…Several studies showed that an auditory stimulus can lead to visual saccades toward the source of the sound (Zahn et al, 1978;Zambarbieri et al, 1982;Van Grootel and Van Opstal, 2009) and that the presentation of an auditory stimulus can reduce the rate of saccades (Rolfs et al, 2005;Kerzel et al, 2010;Yuval-Greenberg and Deouell, 2011;Zou et al, 2012). Moreover, one study has shown evidence that gaze position can affect auditory localization accuracy (Maddox et al, 2014) and results from our team suggest that listening or even imagining auditory motion stimulus can induce involuntary eye movements (Landry et al, 2015). Considering the apparent link between auditory input and oculomotor behaviors, one might wonder how the loss of auditory input from birth might influence these motor behaviors.…”
Section: Introductionsupporting
confidence: 58%
“…The presence of a peripheral substrate shared by processes underlying production and perception would also have implications for our understanding of auditory imagery and auditory short-term memory (ASTM): first, because frontoparietal, cerebellar, and sensorimotor areas active in perception overlap those active in imagery (Harris & de Jong, 2015; Herholz, Halpern, & Zatorre, 2012; Landry et al, 2015; Lima et al, 2015), and second, because common mechanisms are thought to underpin perception and imagery, with perception favoring ventral pathways and imagery, the dorsal pathway. One suggestion is that this overlapping activity reflects sensorimotor simulation (Lima et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…If confirmed, the dependence of auditory processing (in part) on autonomic pathways and the limbic system would offer a new way of investigating processes that underlie our relationship with sound, particularly the sounds of speech, song, and music: From a bodily perspective, it is possible to see connections that are difficult to appreciate from a top-down direction; for example, (a) direct connections between cranial nerves V, VII, IX, and X, and NTS (important in regulation of cardiovascular functions such as blood pressure and heart rate control) may help explain why music has such a powerful influence on the cardiovascular system (Nieuwenhuys et al, 2008, p. 706), (b) projection of listening-related activity to orofacial regions of the primary sensory and (subsequently) motor cortex, may be relevant in the search to understand why motor regions of the brain are recruited in perception and why these regions are modulated by the size of the music interval (Royal et al, 2015), and (c) the projection of pitch-related patterns of activity via autonomic pathways to centers that play a key role in emotion processing may be relevant in the search to understand why there is such a close relationship between music and emotion. The presence of a peripheral substrate shared by processes underlying production and perception would also have implications for our understanding of auditory imagery and auditory short-term memory (ASTM): first, because frontoparietal, cerebellar, and sensorimotor areas active in perception overlap those active in imagery (Harris & de Jong, 2015;Herholz, Halpern, & Zatorre, 2012;Landry et al, 2015;Lima et al, 2015), and second, because common mechanisms are thought to underpin perception and imagery, with perception favoring ventral pathways and imagery, the dorsal pathway. One suggestion is that this overlapping activity reflects sensorimotor simulation (Lima et al, 2015).…”
Section: Discussionmentioning
confidence: 99%